Seasonal trends and retention of polycyclic aromatic compounds (PACs) in a remote sub-Arctic catchment - Nguyen, Minh A.; Ahrens, Lutz; Gustavsson, Jakob; Laudon, Hjalmar; Wiberg, Karin (2023)
Atmospheric deposition is the most dominant source of polycyclic aromatic hydrocarbons (PAHs) in remote and pristine areas. Despite low bioaccumulation potential, PAHs and their persistent transformation products (PAHderivatives) are chemicals of concern as they can harm human and animal health through chronic low dose exposure. In this study, atmospheric deposition fluxes of polycyclic aromatic compounds (PACs) were measured on a seasonal basis (3-month periods) from 2012 to 2016 in a remote subarctic forest catchment in northern Europe. The target PACs included 19 PAHs and 15 PAH-derivatives (oxygenated, nitrogenated, and methylated PAHs). The deposition fluxes of Sigma PAHs and Sigma PAH-derivatives were in the same range and averaged 530 and 500 ng m(2) day(-1), respectively. The fluxes were found to be higher with a factor of 2.5 for Sigma PAHs and a factor of 3 for.PAH-derivatives during cold (10 degrees C) periods. PAHs and PAH-derivatives showed similar seasonal patterns, which suggests that these two compound classes have similar sources and deposition mechanisms, and that the source strength of the Sigma PAH-derivatives in air follows that of the PAHs. The terrestrial export of PACs via the outlet of the catchment stream was estimated to be 1.1% for.PAHs and 1.7% for Sigma PAH-derivatives in relation to the annual amounts deposited to the catchment, which suggests that boreal forests are sinks for PACs derived from the atmosphere. Some individual PACs showed higher export than others (i.e. chrysene, cyclopenta(c,d)pyrene, carbazole, quinoline, and benzo(f)quinoline), with high export PACs mostly characterized by low molecular weight and low hydrophobicity (2-3 benzene rings; log K-ow<6.0).